The Desert Grassland - Van Devender, Thomas R.; McClaran, Mitchel P., 1956- (Book collections on Project MUSE., 1995)
The mixed grass and shrub vegetation known to scientists as desert grassland is common to the basins and valleys that skirt the mountain ranges throughout southwestern North America, extending from Arizona, New Mexico, and Texas down through thirteen Mexican states. Leading experts in geography, biology, botany, zoology, and geoscience present new research on the desert grassland and review a vast amount of earlier work. They reveal that present-day grasses once grew in the ice age forests that existed in these areas before the climate dried and the trees vanished, and how the intensity and frequency of fire can influence the plant and animal species of the grassland. They also document how the influence of humans - from Amerindians to contemporary ranchers, public land managers, and real estate developers - has changed the relative abundance of woody and herbaceous species and how the introduction of new plants and domesticated animals to the area has also affected biodiversity. The book concludes with a review of the attempts, both failed and successful, to reestablish plants in desert grasslands affected by overgrazing, drought, and farm abandonment.